Patterns of Alcohol Use Among Patients Living with HIV in Urban, Large Rural, and Small Rural Areas - Bensley, Kara M. (J Rural Health, 2018)
BACKGROUND: For people living with HIV (PLWH), alcohol use is harmful and may be influenced by unique challenges faced by PLWH living in rural areas. We describe patterns of alcohol use across rurality among PLWH. METHODS: Veterans Aging Cohort Study electronic health record data were used to identify patients with HIV (ICD-9 codes for HIV or AIDS) who completed AUDIT-C alcohol screening between 2/01/08 and 9/30/14. Regression models estimated and compared 4 alcohol use outcomes [any use (AUDIT-C > 0) and alcohol use disorder diagnoses (AUD; ICD-9 codes for abuse or dependence) among all PLWH; and AUDIT-C risk categories: lower- (1–3 men/1–2 women), moderate- (4–5 men/3–5 women), higher- (6–7), and severe-risk (8–12), and heavy episodic drinking (HED; ≥1 past-year occasion) among PLWH reporting use] across rurality (urban, large rural, small rural) and census-defined region. FINDINGS: Among 32,699 PLWH (29,540 urban, 1,301 large rural, and 1,828 small rural), both any alcohol use and AUD were highest in urban areas, although this varied across region. Predicted prevalence of any alcohol use was 54.1% (53.5%−54.7%) in urban, 49.6% (46.9%−52.3%) in large rural, and 50.6% (48.3%−52.9%) in small rural areas (P < .01). Predicted prevalence of AUD was 14.4% (14.0%−14.8%) in urban, 11.8% (10.0%−13.5%) in large rural, and 12.3% (10.8%−13.8%) in small rural areas (P < .01). Approximately 12% and 25% had higher- or severe-risk drinking and HED, respectively, but neither differed across rurality. CONCLUSION: Though some variation across rurality and region was observed, alcohol-related interventions are needed for PLWH across all geographic locations.